The last best hope - McCormack, Una (Star trek: Picard, 2020)
"An original novel based on the new Star Trek TV series! A thrilling novel leading into the new CBS series, Una McCormack's The Last Best Hope introduces you to brand new characters featured in the life of beloved Star Trek captain Jean-Luc Picard--widely considered to be one of the most popular and recognizable characters in all of science fiction"--